2019
DOI: 10.3389/fonc.2019.00220
|View full text |Cite
|
Sign up to set email alerts
|

IRF6 Is Directly Regulated by ZEB1 and ELF3, and Predicts a Favorable Prognosis in Gastric Cancer

Abstract: Interferon regulatory factor 6 (IRF6) acts as a tumor suppressor and controls cell differentiation in ectodermal and craniofacial tissues by regulating expression of target genes. However, its function in gastric cancer (GC) remains unknown to date. In this study, we found that the IRF6 expression was significantly downregulated in GC. And the decreased expression of IRF6 was clinically correlated with poor prognosis of GC. Moreover, loss-of-function and gain-of-function studies showed that IRF6 was negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 41 publications
1
45
1
Order By: Relevance
“…15 IRF6 expression was shown to be significantly decreased in gastric cancer, and gastric cancer patients with lower expression of IRF6 are predicted to have a shorter overall survival time and disease-free time. 18 Recent studies have confirmed that IRF6 can be regulated by multiple transcription factors, such as tumor protein 63, zinc finger E-box binding homeobox 1 and E74-like ETS transcription factor 3. 18,32 Moreover, miRs, as post-transcriptional regulators, are negatively related to the expression of target genes by fully or partially binding with their 3'-UTRs to repress mRNA and/or protein expression.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…15 IRF6 expression was shown to be significantly decreased in gastric cancer, and gastric cancer patients with lower expression of IRF6 are predicted to have a shorter overall survival time and disease-free time. 18 Recent studies have confirmed that IRF6 can be regulated by multiple transcription factors, such as tumor protein 63, zinc finger E-box binding homeobox 1 and E74-like ETS transcription factor 3. 18,32 Moreover, miRs, as post-transcriptional regulators, are negatively related to the expression of target genes by fully or partially binding with their 3'-UTRs to repress mRNA and/or protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…16,17 However, IRF6 does not participate in mediating the gene expression of interferon. 18 Intriguingly, IRF6…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the tissue repair phenotype is added to the list of other malfunctions observed in the heterozygous mouse (ie, brain volume, endotoxic shock response) validating this model as a powerful tool to understand IRF6‐related human conditions. As recent reports continue to implicate IRF6 in cancer, and the well‐established link between chronic wounds and cutaneous carcinogenesis, this model could be a great tool to further investigate this aspect of IRF6 biology.…”
Section: Discussionmentioning
confidence: 99%
“…The primers for wildtype and mutant CCND1 3'UTR were as follows, F: 5'-gggagctcCTGTCCCACTC CTACGATAC-3', R1 (wildtype): 5'-tctctagaTGTAACATCAAAGGCAGAAGG-3', R2 (Mutant): 5'-tctctagaTGTTTTTTCAAAGGCAGAAGGTTTGTGT-3'. The luciferase reporter assay was conducted as we previously described before [14]. Brie y, the BGC823 cells were seeded into 12-well-tissue plates 24h before transfection, and then co-transfected with 5 nM siRNA and 1mg plasmid using the Lipofectamine 2000 Reagent (Invitrogen), according to the manufacturer's instructions.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%